Contamination of ritual: the space of Ukrainian House and its performing (City: History, Culture, Society, 2025)
The starting point of this study is the hypothesis that an architecturally mediated place — network node and center of ideology — is the territory of permanent influence, which is capable to reproduce programmed relations regime and adjust social spaces in accordance to it. The unusual tension emerges in relations with places-remains of political systems of the past: connected to another context they become an anachronistic surplus, differently integrated to the surrounding. Totalitarian architectural memorials are of this kind — ideologically strengthened agents of socialization, whose political role is destabilized or transformed into new meaning. Several examples are considered in this article in order to demonstrate different positions in dealing with difficult architectural heritage, but Lenin’s Museum building in Kyiv is explored most of all. It has been appropriated by the Ukrainian House, a representative institution, which inherited established ways of positioning and relation models — often active in new forms of representation. These ways are legitimized due to insensibility and purposeful forgetfulness. That’s why an effective subversion is a demand and it requires a critical interaction with architectural space, but not with a denotation system. The art as a spatial practice can be such an instrument: it displays and changes characters of place, demonstrates unobvious conflicts and proposes side reality. Using the example of temporary exhibition “How are you?” in Ukrainian House — the installation of wartime art which is situationally appropriated and performed the architectural space — it has been revealed the contact points which could be useful in intentional rethinking of architectural memorial and developing strategies of productive interaction. The spatial model of Henri Lefebvre, character category of Christian Norberg-Schulz and theory of territorialized assemblage of Kim Dovey were useful in this research
Keywords: place; space; characters; totalitarian architecture; the Ukrainian House; installation; exhibition “How are you?”